Dampak implementasi Massive Open Online Course (MOOC) di berbagai negara - Dewi, May Prastika; Rahmawati, Selly (Universitas Negeri Yogyakarta, 2024)
This study aims to determine and explain the impact of implementing the Massive Open Online Course (MOOC) in various countries. Especially on student participation or commitment, student satisfaction, and student learning outcomes in the implementation of knowing and explaining the impact of implementing the Massive Open Online Course (MOOC) in various countries. The research method in this study is a systematic literature review research method. Literature review is a research method that involves describing or outlining relevant literature for a particular topic or field. This study carried out a review with 9 articles consisting of 7 international articles and 2 national articles. The results of the study show that: 1) student engagement is influenced by web-based learning self-efficacy, commitment, money incentives, academic self-efficacy, teacher teaching presence, perceived benefits, metacognition, independent learning, and challenge and control have a limited role in participant involvement educate; 2) student satisfaction is influenced by the ease of use and benefits felt by students; and 3) Massive Open Online Course (MOOC) has an effect on student learning outcomes and can improve student learning outcomes.